PENGARUH SENSE OF BELONGING TERHADAP EMPLOYEE ENGAGEMENT PADA PEGAWAI KEMENTERIAN PEKERJAAN UMUM DAN PERUMAHAN RAKYAT (PUPR) BALAI WILAYAH SUNGAI SUMATRA II - Khatarina Ginting; Karina Meriem Beru Brahmana; Hotpascaman Simbolon (Jurnal Psikologi Universitas HKBP Nommensen, 2022)
This study aims for the purpose of this study is to see the effect of sense of belonging on employee engagement of employees of the Ministry of Public Works and Public Housing (PUPR) Balai Wilayah Sungai Sumatra II. This research was conducted on employees of the Ministry of Public Works and Public Housing, Balai Wilayah Sungai Sumatra II with a total of 78 employees as respondents using a random sampling method. The data collection technique used a psychological scale, namely the Linkert scale. The data obtained were analyzed using a simple linear regression technique using the SPSS 25.0 application. The results of this study indicate that the sense of belonging has an effect on employee engagement in the employees of the Ministry of PUPR, Balai Daerah Sungai II Sumatra.